2019
DOI: 10.1515/chem-2019-0075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of xanthan gum addition on phenolic acids composition and selected properties of new gluten-free maize-field bean pasta

Abstract: Replacing the gluten network to produce high quality pasta is a great technological challenge. One of known solutions to the problem is the addition of xanthan gum. This paper focuses on the possibility of obtaining a new type of gluten-free maize-field bean pasta and explores the characteristics of phenolics content, antioxidant activity, cooking quality, textural and thermotropic behavior as well as the microstructure of pasta products with the various levels of added xanthan gum. The obtained results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Besides, addition of gum results in the development of continuous protein network, which reduces pasta adhesiveness. Padalino et al (2013) and Widelska et al (2019) also observed that the hydrocolloid addition to the gluten-free pasta formulation led to the decrease in adhesiveness. Other textural attributes including cohesiveness, springiness, gumminess, and chewiness also increased with the addition of gum in pasta formulation.…”
Section: Textural Properties Of Pastamentioning
confidence: 91%
See 1 more Smart Citation
“…Besides, addition of gum results in the development of continuous protein network, which reduces pasta adhesiveness. Padalino et al (2013) and Widelska et al (2019) also observed that the hydrocolloid addition to the gluten-free pasta formulation led to the decrease in adhesiveness. Other textural attributes including cohesiveness, springiness, gumminess, and chewiness also increased with the addition of gum in pasta formulation.…”
Section: Textural Properties Of Pastamentioning
confidence: 91%
“…The cooked weight of HCN pasta samples increased from 9.57/5 g to 12.39g/5 g with an increase in the concentration of gum used. The rise in cooked weight may be related to water-binding and water-holding capacity of the gum used for the preparation of pasta (Widelska et al, 2019).…”
Section: Cooking Characteristics Of Pastamentioning
confidence: 99%
“…After hydrating this hydrocolloid, it can fill up any free space in the system, which makes dough structure stronger. As a previous study reports [47], adding up to 1% XG to corn-bean pasta results in a more compact internal structure with visible starch granule agglomerates embedded in the fibrous protein-gum matrix. In line with these results, it would be interesting to employ a XG concentration of approximately 0.6% to achieve improved textural characteristics to approach the sought "al dente" point.…”
Section: Mechanical Properties Of the Uncooked And The Cooked Fresh Egg Pastamentioning
confidence: 51%
“…Hydrocolloids could bind large amounts of water; the more water they bind, the faster heat will transfer (Nussinovitch, 1997). Apart from the above, positive association between starch and hydrocolloid might restrict the phase transition and mobility of starch chain (Widelska et al, 2019), as noted in samples with high gum fraction.…”
Section: Cooking Qualitymentioning
confidence: 93%